Umami taste, free amino acid composition, and volatile compounds of brown seaweeds - Mouritsen, Ole G.; Duelund, Lars; Petersen, Mikael Agerlin; Hartmann, Anna Loraine; Frøst, Michael Bom (Journal of applied phycology, 2019)
Umami taste is associated with deliciousness and was first suggested as a basic taste by Kikunae Ikeda in 1909 when he discovered that the brown seaweed konbu ( Saccharina japonica ), used to provide aqueous extracts for the Japanese soup stock dashi , contains very large amounts of free glutamate. We have performed a comparative analysis of the free amino acid contents of 20 different species of brown seaweeds used for human consumption from around the world, belonging to the 12 genera Nereocystis , Macrocystis , Laminaria , Saccharina , Undaria , Alaria , Postelsia , Himanthalia , Ecklonia (former Eisenia ), Sargassum , Fucus , and Corda . We furthermore measured mineral and iodine contents as well as identified a range of volatile compounds and estimated their influence on the perception of umami taste. The results provide a basis on which chefs and food producers can control umami sensation in food items using some of the most popular species of edible brown seaweeds.